PEMBUATAN ECOBRICK DARI SAMPAH PLASTIK MENJADI BARANG YANG BERMANFAAT - Sulistiyono, Heri; Putra, Adeyong Wira; Taufik, Baiq Nabila; Khakiki, Bintang Dwi Nur; Rahmatun, Dwiana Aulya; Utami, Fadillah Rabbiatul; Rahayu, Nita Agustini; Ramdani, Nofi; Wilujeng, Putri Rahayu; Frasitio, Rizal Hadi; Triyani, Wiwin Akarena (Universitas Mataram, 2023)
Batujai Village is one of the villages in West Praya District, Central Lombok Regency. This village has a fairly dense population, with this large population, of course, the volume of waste is increasing. Because of this, what underlies PMD KKN students in Batujai Village, Mataram University in 2023 to make products in the form of ecobrick by recycling 3R (Reduce, Reuse, Recycle) waste. Through the work program that has been attempted, it has succeeded in reducing the volume of waste disposed of by the community at TPS, in accordance with the purpose of carrying out this activity, which is to reduce the volume of waste by converting plastic waste into more useful items